Factors that Influencing Tourists Revisit Intention - Barkah, Barkah; Febriasari, Puty (JDM (Jurnal Dinamika Manajemen), 2021)
The results of previous research indicate that novelty-seeking through travel is one of the keys to tourist satisfaction. In the context of tourism, destination image and tourist satisfaction are usually used to predict the revisit intention to certain tourist destinations. This research is designed to study the formation of tourist satisfaction and their motivation to return to Pontianak City based on experiences on previous visits. Novelty-seeking, destination image, and quality of culinary experience are proposed to be predictors of tourist satisfaction and intention to return. The results of the study using SEM-PLS show that basically tourist satisfaction and intention to return are determined by the quality of previous travel experiences and the image of tourist destinations. The coefficient of determination of the quality of the tourist’s culinary experience and the image of the destination in the research model is quite small, therefore it is necessary to carry out further research to identify the factors that influence tourist satisfaction and the intention of returning to visit in the context of tourism.